Land scarcity and input intensification in smallholder irrigated agriculture in Egypt - Abay, Kibrom A.; El-Enbaby, Hoda; Abdelfattah, Lina Alaaeldin; Breisinger, Clemens (International Food Policy Research Institute, 2021)
Increasing population pressure and population density in many African countries are inducing land scarcity and land constraints. These are expected to trigger various responses and adaptation strategies, including agricultural intensification induced by land scarcity, as postulated by the Boserup hypothesis. However, most empirical evaluations of the hypothesis come from rainfed agriculture and mostly from sub-Saharan Africa, where application of agricultural inputs remains historically low. Agricultural intensification practices and the relevance of the Boserup hypothesis in irrigated agriculture (and where application of improved inputs is high) remains unexplored. We investigate the implication of land scarcity on agricultural intensification and the relevance of the Boserup hypothesis in the context of Egypt, where agriculture is dominated by irrigation and input application rates are much higher than elsewhere in Africa. We find that land scarcity increases overapplication of nitrogen fertilizer relative to crop-specific agronomic recommendations. This implies that land constraints remain as important challenges for sustainable agricultural intensification. Finally, we find suggestive evidence that such overapplication of nitrogen fertilizers is not yield-enhancing, but, rather, yield-reducing. We also document that land scarcity impedes mechanization of agriculture.